2016
DOI: 10.1186/s12935-016-0311-8
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide promotes genomic and phenotypic changes in glioblastoma cells

Abstract: BackgroundTemozolomide (TMZ) is a first-line drug for the treatment of glioblastoma. Long-term TMZ-treated tumour cells acquire TMZ resistance by profound reprogramming of the transcriptome, proteome, kinome, metabolism, and demonstrate versatile and opposite changes in proliferation, invasion, in vivo growth, and drug cross-resistance. We hypothesized that chromosomal instability (CIN) may be implicated in the generation of TMZ-driven molecular and phenotype diversity. CIN refers to the rate (cell-to-cell var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 62 publications
2
37
0
Order By: Relevance
“…Experiments have suggested that intense hypoxia following anti-angiogenic treatments can select for invasive cell phenotypes as an adaptive response to hypoxia due to lack of vessels (19). In addition, new data suggest that long-term temozolomide treatment induces chromosomal instability, which in turn leads to potential increases in invasion and migration (38). Including such additional phenotypic changes in our model, as well as therapy-induced reprogramming of differentiated GBM cells to GSCs (35), would only add to the invasiveness we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have suggested that intense hypoxia following anti-angiogenic treatments can select for invasive cell phenotypes as an adaptive response to hypoxia due to lack of vessels (19). In addition, new data suggest that long-term temozolomide treatment induces chromosomal instability, which in turn leads to potential increases in invasion and migration (38). Including such additional phenotypic changes in our model, as well as therapy-induced reprogramming of differentiated GBM cells to GSCs (35), would only add to the invasiveness we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation was also found to activate NF-jB/STAT3 cooperative signaling that was linked to increased expression of intercellular adhesion molecule-1 (ICAM-1) and cell invasion (Kesanakurti et al, 2013). The standard chemotherapeutic TMZ was reported to select for GBM cells with different properties than the parental cells including an increase in migration and invasion and upregulation of EMT markers like SNAI1 and SNAI2 (Stepanenko et al, 2016). As earlier mentioned, treatment with the VEGF inhibitor causes MT in a hypoxia-dependent manner eventually establishing therapy-resistant cells (Piao et al, 2013).…”
Section: Mt and Response To Therapymentioning
confidence: 99%
“…Stepaneko et al extended these findings with in vitro studies that demonstrated that long-term exposure of glioma cells to TMZ induces chromosomal instability, leading to alteration of cell growth, invasiveness, migration, and response to retreatment (69). Among the TMZ-resistant cell lines, some responded to temsirolimus, an mTOR inhibitor.…”
Section: Temozolamide and Lgg Progressionmentioning
confidence: 56%